RESEARCH ON LOCAL PROTECTION AGAINST PLASMA NITRIDING USING SPECIAL PAINTS WITH COPPER POWDERS AND MAGNESIA BINDING MATTER SISTEMS - Marius BIBU; Florin CIOFU (Fiabilitate şi Durabilitate)
As a result of the investigations concerning the elaboration of efficient technologies for local protection of metallic pieces with isolated coats against plasma nitriding, two variants of special paints were elaborated. Those are based on lamella copper powder with a lime magnesia binding system, in which polystyrene was added in an organic solvent. The paper analyses the advantages as a result of the usage in a mixture of magnesium oxide with carbon tetrachloride, advantages as a result of the experiments done with selected types of paints (samples subjected to ionic nitriding in a period of 15 hours at a temperature of 5300C). To check the efficiency of the protection of the elaborated paints, experiments were done comparatively on not protected metallic surfaces (steel 39MoAlCr15) and on metallic surfaces protected by protector films put in three variants of different thickness.